Communication Component of Accounting Policy of Enterprise - Муравський, В. В. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
The communications components of accounting policy are justified for effective management of the enterprise in the article. The aim of the research is to analyze the influence of accounting policy elements on the communications processes in management. The task is to select elements of accounting policy that influence on accounting communications organization. Methods of analysis and synthesis used to structure the substantive research-based identification and formalization of the of communication components of accounting policy in the context of management. Expediency proved to generate significant accounting policies of communication organization oriented the reliable information. The study highlights the forming of the communications accounting policy through the prism of selection of it organizational, technical, methodical levels in financial, administrative accounting and tax calculations. This result will be useful for application in entities of all legal forms and fields of activity. The result of the study has theoretical and practical value in terms of selection of optimal fea-tures models accounting policy for enterprises.